Shpet, the ships and the Silver Age: on demythologising Russian philosophy - Bourgeot, Liisa (Studies in East European thought, 2025)
The centennial of the infamous Philosophers’ Ships ( filosofskii parokhod ) in 2022 offered an opportunity to examine the story that has been evolving around those involved since the end of the Soviet era. This article discusses the place of Gustav Shpet in the myth of the 1922 steamers. Although he never boarded the steamers, Shpet has come to be associated with their story. In asking why this is the case, the article explores the ships’ history as a part of the popular conception of Russian ‘Silver Age’ philosophy. It suggests that this concept developed during the post-Soviet search for an ‘authentically’ Russian philosophical identity and under the strong influence of Nikolai Berdyaev’s émigré era texts on Russian messianism. An examination of Shpet’s and Berdyaev’s parallel philosophical developments between 1916 and 1922 showcases the differences between the two thinkers. The article proposes that Shpet’s philosophy is indeed incompatible with the popular Silver Age narrative and that this narrative, therefore, is in need of revision.